Table Turning in the Early 1850s: The Séance Reports of Agénor de Gasparin - Alvarado, Carlos S. (Journal of Scientific Exploration, 2018)
The phenomena of table turning flourished during the 1850s, providing for many the context for belief in spirit action, and for the development of explanations such as unconscious muscular movements and the exteriorization of nervous forces from the sitters. This paper consists of the presentation of excerpts from the classic study of these phenomena by Agénor de Gasparin, who reported his work on the subject in his book Des Tables Tournantes (1854, 2 vols., translated to English in 1857). De Gasparin believed that unconscious muscular action could not explain the movements of tables, and postulated the emission of a force from the sitters around the table to account for the movements. I present a long excerpt from de Gasparin’s book in which he described the phenomena he obtained, preceded by a short review of interest in table phenomena in the 1850s, and followed by critiques showing the general skepticism about these phenomena during and after de Gasparin’s lifetime.